2019
DOI: 10.1016/j.omtn.2019.02.003
|View full text |Cite
|
Sign up to set email alerts
|

RNA-Based Therapy Utilizing Oculopharyngeal Muscular Dystrophy Transcript Knockdown and Replacement

Abstract: Oculopharyngeal muscular dystrophy (OPMD) is caused by a small expansion of a short polyalanine (polyAla) tract in the poly(A)-binding protein nuclear 1 protein (PABPN1). Despite the monogenic nature of OPMD, no treatment is currently available. Here we report an RNA replacement strategy that has therapeutic potential in cell and C. elegans OPMD models. We develop selective microRNAs (miRNAs) against PABPN1, and we report that miRNAs and our previously developed hammerhead ribozymes (hhR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Although we detected a small but significant decrease in Becn1 RNA (Figure 6H) when Ct values from siPab samples were normalized to Ct values from siScr samples, there was no significant difference when compared to non-transfected cells (Supplementary Figure S6A) and no defect in autophagosome formation was detected in Pabpn1 knockdown cells (Figure 6I). Previous studies have suggested that a combination of exogenous recombinant PABPN1 and endogenous Pabpn1 knockdown is sufficient to rescue muscle phenotypes in A17.1 mice (Malerba et al, 2017;Abu-Baker et al, 2019;Malerba et al, 2019a). We transfected Pabpn1 +/+ and Pabpn1 +/A17 pharyngeal myoblasts with plasmids encoding FLAG-tagged human PABPN1 (FL-hsPABPN1) (Banerjee et al, 2019) or FL-hsPABPN1 along with siRNA targeting Exon 7 of murine Pabpn1.…”
Section: Resultsmentioning
confidence: 99%
“…Although we detected a small but significant decrease in Becn1 RNA (Figure 6H) when Ct values from siPab samples were normalized to Ct values from siScr samples, there was no significant difference when compared to non-transfected cells (Supplementary Figure S6A) and no defect in autophagosome formation was detected in Pabpn1 knockdown cells (Figure 6I). Previous studies have suggested that a combination of exogenous recombinant PABPN1 and endogenous Pabpn1 knockdown is sufficient to rescue muscle phenotypes in A17.1 mice (Malerba et al, 2017;Abu-Baker et al, 2019;Malerba et al, 2019a). We transfected Pabpn1 +/+ and Pabpn1 +/A17 pharyngeal myoblasts with plasmids encoding FLAG-tagged human PABPN1 (FL-hsPABPN1) (Banerjee et al, 2019) or FL-hsPABPN1 along with siRNA targeting Exon 7 of murine Pabpn1.…”
Section: Resultsmentioning
confidence: 99%
“… 5 Gene replacement in this case would require a codon-optimized transgene to avoid being silenced by the RNAi or antisense oligonucleotide treatment. This approach has proved beneficial for oculopharyngeal muscular dystrophy in preclinical mouse studies and in theory could be applied to any of the previously mentioned disease categories 31 …”
Section: Genetic Treatment Strategies Employed In Neuromuscular Medicinementioning
confidence: 99%
“…This approach has proved beneficial for oculopharyngeal muscular dystrophy in preclinical mouse studies and in theory could be applied to any of the previously mentioned disease categories. 31 Knockdown treatments are not yet clinically available for dominantly inherited myopathies. Several studies are currently in preclinical development for disorders such as facioscapulohumeral muscular dystrophy and centronuclear myopathy due to DNM2 mutations.…”
Section: Commentmentioning
confidence: 99%
“…Concerning nucleic acid-based therapy, RNA therapy has shown promising results in treating several human malignances [ 98 , 99 , 100 ], including viral diseases [ 101 ]. There are different approaches to targeting RNA in the human body: antisense oligonucleotides (ASOs) [ 102 ], microRNAs (miRNAs) [ 103 ], small interfering RNAs (siRNAs) [ 104 ], RNA vaccines [ 105 , 106 ], and CRISPR/Cas systems [ 101 ], among others. Nevertheless, due to poor RNA stability inside the body [ 107 ], inefficient delivery to the target site, and low bioavailability [ 108 , 109 ], RNA delivery remains one of the biggest challenges in RNA therapy [ 104 , 110 ].…”
Section: The Landscape Of Nucleic Acid-based Therapies In Sars-cov-2mentioning
confidence: 99%